Legal protection for wives in the encumbrance of joint marital property as collateral in sharia financing: Toward a substantive consent–notarial or PPAT prudence model - Ahmad Mubarak; Novy Listiana; Nisa Adelia; Habibah Lestari (Priviet Social Sciences Journal, 2026)
This article examines the legal protection of wives in the encumbrance of joint marital property as collateral in sharia financing agreements executed before a notary. In practice, collateral objects used in sharia financing, especially land or houses, are often registered under the husband’s name, although they were acquired during marriage and therefore constitute joint marital property. This situation may place the wife in a vulnerable position when her consent is treated merely as a formal administrative requirement. This research uses normative legal research with statutory and conceptual approaches. The legal materials consist of primary legal materials, including marriage law, notarial law, sharia banking law, mortgage law, and the Compilation of Sharia Economic Law, as well as secondary legal materials from books and legal journals. The study finds that the wife’s consent in the encumbrance of joint property must not be reduced to a mere signature in the notarial deed. Such consent must be understood as a substantive legal protection mechanism based on awareness, voluntariness, and adequate legal understanding. Notaries have a preventive role in ensuring the legal status of the collateral object, the capacity and free will of the parties, and the conformity of the deed with the principles of justice and prudence in sharia financing. Therefore, the notary’s role is essential in protecting the wife’s economic rights and preventing future disputes.